Collective Bargaining in Catholic Schools: What Does Governance Have to Do With It? - James, John T. (Catholic Education: A Journal of Inquiry and Practice, 2004)
This article outlines the significant legal decisions regarding collective bargaining in Catholic Schools, identifies the governance structures employed in Catholic schools and the methods of translating these governance structures into documents required by civil law, and concludes with the citation of two recent court decisions that demonstrate the method of incorporation and the day-to-day governance practices utilized in Catholic schools that are of great importance to educational leaders.